IMPROVING STUDENTS SPEAKING SKILL USING PROJECT BASED LEARNING AT THE EIGHTH GRADE OF SMPN 9 JANGKANG - Sandefer, Marchely Henes; Anita, Finny; Kurniawati, Tri (IKIP PGRI Pontianak, 2024)
Abstract The purpose of this study is to find out how project based learning can help students improve their speaking skills. Classroom Action Research (CAR) was used to conduct this study. Students of SMPN 9 Jangkang who are in grade eight-b are the subjects of this study. This study used observation sheets and speaking tests to collect data. The data shows that project based learning improves students' speaking skills by helping them build sentences, speak fluently, share ideas confidently, and stay motivated while learning. In addition, it improves overall speaking ability by making lessons easier to understand. Keywords: project based learning, speaking skills, classroom action research.